Organocatalytic dynamic kinetic resolution via conjugate addition: synthesis of chiral trans-2,5-dialkylcyclohexanones - Pandey, Ganesh; Adate, Priyanka A.; Puranik, Vedavati G. (Organic & Biomolecular Chemistry, 2012)
A novel strategy of initiating an organocatalysed dynamic kinetic resolution (dr up to 99 : 1 and er up to 94 : 6) for the synthesis of chiral trans-2,5-dialkylcyclohexanones by an asymmetric conjugate addition of dimethyl malonate on to 6-substituted cyclohexenones is reported.